2018
DOI: 10.1111/joss.12441
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of NaCl with KCl in bread: Effect on sensory characteristics and consumer perception

Abstract: Sodium reduction strategies that fully or partially compensate for the effect of reducing sodium on the sensoy profile of foods have been proposed as a cost‐effective alternative to decrease dietary sodium intake at the population level. The present work aimed at exploring the effect of partially replacing NaCl with KCl on the sensory characteristics and hedonic perception of toast bread. Equivalent salty concentration of NaCl : KCl blends were estimated relative to different NaCl concentrations, using paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
(67 reference statements)
2
7
0
Order By: Relevance
“…KCl’s feasibility as a salt replacer was investigated in wheat bread by Antúnez et al . (2018). A trained panel characterised bread containing a variety of NaCl:KCl blends using a temporal Check‐All‐That‐Apply method and found that substituting 30% NaCl produced a bread with a similar sensory profile, although once substitution levels reached 40% and above, an increase in the observation of a metallic attribute occurred.…”
Section: Current Activitymentioning
confidence: 99%
“…KCl’s feasibility as a salt replacer was investigated in wheat bread by Antúnez et al . (2018). A trained panel characterised bread containing a variety of NaCl:KCl blends using a temporal Check‐All‐That‐Apply method and found that substituting 30% NaCl produced a bread with a similar sensory profile, although once substitution levels reached 40% and above, an increase in the observation of a metallic attribute occurred.…”
Section: Current Activitymentioning
confidence: 99%
“…Most previous studies involving sodium-reduced food products have used static approaches for the sensory characterization of products rather than dynamic methodologies. However, in the last decade, an increasing number of studies have addressed the effect of salt reduction on the temporal sensory profile of different food categories such as sausages and ham, cheese, cream cheese, butter, margarine, bread and shoestring potatoes [17][18][19][20][21][22][23][24][25][26][27][28]. Temporal sensory methods have proven useful for understanding the impact of sodium reduction during reformulation processes [10].…”
Section: Introductionmentioning
confidence: 99%
“…CATA testing has been identified by multiple reports as appropriate for the determination of whether the product has specific sensory flavor characteristics, including flavors, suggesting that it is appropriate for use in these specific circumstances. For example, it has been used to examine products such as bread (Antúnez, Giménez, Vidal, & Ares, ), strawberries (Oliver, Cicerale, Pang, & Keast, ), beer (Reinbach, Giacalone, Bredie, Machado Ribeiro, & Bom Frøst, ), cosmetics (Parente, Ares, & Manzoni, ), and many other products.…”
Section: Results and Discussion—phase 1: Pilot Sensory Testmentioning
confidence: 99%